Metal-Free ATRP Catalyzed by Visible Light in Continuous Flow - El Achi, Nassim; Bakkour, Youssef; Adhami, Wissal; Molina, Julien; Penhoat, Maël; Azaroual, Nathalie; Chausset-Boissarie, Laëtitia; Rolando, Christian (Frontiers in Chemistry, 2020)
ATRP of methyl methacrylate catalyzed by Eosin Y, an inexpensive and an environmental benign dye, was performed in a continuous flow reactor made of FEP tubing and irradiated by visible light green LEDs. The reaction under flow conditions was significantly more rapid and controlled compared to that in batch giving 90% of polymerization after only 3 h of irradiation. The formed polymers in flow have Mn measured by GPC and DOSY NMR in accordance with the theoretical values and show low dispersities (Đ < 1.5). The livingness of the polymers has been confirmed by LEDs on and LEDs off experiments and by the synthesis of block copolymers. The protocol described herein serves as a “proof of concept” of using Eoin Y as a photocatalyst for controlled polymerization and of using 1D and 2D- NMR for polymer characterization. The protocol could be replicated in the future for other reversible-deactivation radical polymerizations.